Pembuatan Handsoap Antibakteri Dan Pelembap Kulit Berbasis Minyak Jelantah Dan Minyak Zaitun Dengan Proses Saponifikasi - Bakhri, Syamsul; Gusnawati, Gusnawati; Wahyu Lestari, Tri Isra; Zainal, Zakinah; Fidya, Nurul (Faculty of Agricultural Technology, Universitas Semarang, 2023)
Previous research used used cooking oil as a handsoap which has a strong inhibition of bacterial growth but still causes dry and slightly itchy skin, so this research was perfected by adding olive oil as a base. The problem is, which formulations of used cooking oil and olive oil in handsoap can inhibit bacterial growth and moisturize the skin, as well as their quality against organoleptic tests, irritation, and high foam. The purpose of this study was to determine the formulation of handsoap which has strong antibacterial properties, moisturizes the skin, and determines its quality against organoleptic tests, irritation, and high foaming. The composition of used cooking oil and olive oil used was 125 gr : 125 gr (Formula 1), 150 gr : 100 gr (Formula 2), 175 gr : 75 gr (Formula 3), and 200 gr : 50 gr (Formula 4). The making of this handsoap uses an experimental method. Testing the zone of inhibition of bacterial growth used the in vitro method, organoleptic testing was done through descriptive tests, and testing for PH, Irritability, and Foam Height was through descriptive tests using observational analytic methods. The results of this study are that this handsoap has a strong ability to inhibit bacterial growth, can moisturize the skin, is not irritated, and has a lot of foam, but has a large PH which is not in accordance with SNI so that it cannot be used by the public